Concentration of some trace elements in falling particulate and soil in vicinity region of Bricks factories in Al-Nassiriya city. - Al-Asadi , Alaa (University of Thi-Qar Journal of Science, 2011)
Abstract The present study aimed to determine the concentration of 4 trace elements (Pb,Cd,Cuand Ni) in the falling particulate and soil in Vicinity region of brick factories in Al-Islahdistrict in Thi-Qar governorate , during the period from Autumn 2009 until Summer 2010 .Samples were collected from six stations, three station with the wind direction and the otherin opposite region, while the seventh station was chousion in right on the wind directionabout 3 Km for from the brick factories. The results were showed regional and seasonalvariations in the concentration of the mentioned metals in both types of samples. The meansannual concentrations of (Pb,Cd,Cu and Ni) in particulate were (111.76,4.14,24.98 and82.43) μg/gm dry weight respectively , while their mean annual concentration in soil were(245.38,6.92,61.30 and 131.17) μg/gm dry weight respectively . Low mean annualconcentrations were recorded in station 7 (reference station) there are(34.31,2.21,19.41,27,2)μg/gm dry weight respectively. The study showed that particulate matter and soil in the study area recorded higherconcentration from the studied elements, while the reference station was recorded lowervalues for all metals under the study. Significant correlations were observed between metalsconcentrations in particulate and soil .In conclusion the effluents of bricks factoriescontribute clearly in supporting the soil by the studied metal through the precipitateparticulate, because of the operation of these factories was by heavy fuel. Also in despite ofthe higher concentration of the metals under the study, but their concentration were in acceptable range , when they compared with the other studies ells where.